Simubis business plan - Maki, Kumail Aqeel Maki Isa (2019)
Simubis develops and sells Insurance education simulation digital games. In the Middle East, insurance training solutions are limited to classroom and self-study with their own limitations. Simubis is a business to business company that sells its products to training institutes and insurance companies along with the associated industries.